Pengembangan Pembelajaran Blended Learning Berbasis Website Di Program Studi Pendidikan Biologi Universitas Samudra - Desy, Ruhama; Setyoko, Setyoko (Jurnal Pendidikan Biologi, 2017)
The development of website based blended learning is aimed to promote change in the acceleration of learning process in higher education which is not bound by space and time, thus will directly improve the quality of learning process in the Study Program of Biology Education of University of Samudra. Utilization of information and communication technology in the development of website based blended learningin higher education combines face to faceand online.Research is functioned as learning mediation between lecturers and students of Study Program of Biology Education of University of Samudra. Research and Development was performed through the model of 4D with stages consisted of Define, Design, Developmentand Disseminatewhich were modified in accordance with the needof researcher. Subjects of experiment were students, lecturers, as well as information and communication technology experts. Instruments of study used were validation sheet and questionnaire. Analysis of qualitative data was done with stages of collecting data, reducing data, presenting data, and drawing conclusion. Result of research based on validation test showed that the validation of media expert was 82.65% with qualification of practical and did not need to be revised, the second validation of teaching expert obtained was 86.25% with qualification of highly practical and did not need to be revisedand validation of respondent by students obtained a value of 90.16% with qualification of highly practical and did not need to be revised. Based on the validation result, the development of website based blended learningis suitable to be used by the students of Biology Education of University of Samudra in learning which combines face to face learning at class and online.